计算:(-4x^3)^2-[(2x)^2]^3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 09:55:55
计算:(-4x^3)^2-[(2x)^2]^3计算:(-4x^3)^2-[(2x)^2]^3计算:(-4x^3)^2-[(2x)^2]^3原式=16x^6-(4x^2)^3=16x^6-64x^6=-
计算:(-4x^3)^2-[(2x)^2]^3
计算:(-4x^3)^2-[(2x)^2]^3
计算:(-4x^3)^2-[(2x)^2]^3
原式=16x^6-(4x^2)^3
=16x^6-64x^6
=-48x^6
(-4X³)² -[(2X)²]³
=16Xˆ6 -64X^6
=-48X^6
原式=(-4)²(x³)²-(2x)^6
=16x^6-64x^6
=-48x^6
2x*4x-3x计算
计算2x X 4x--3x=
计算(x+1)(x+2)(x+3)(x+4)
如何计算 (x+1)(x+2)(x+3)(x+4)
计算(X-1)(X-2)(X-3)(X-4)
(x-1)(x-2)(x-3)(x-4)-24计算
计算:[(x^2 - 4)/(x^2 - x - 6) + (x+2)/(x-3)] / (x+1)/(x-3)
计算:(-x^4)^3-(x^2)^6
x(x-2)(2x-3)计算
计算: (x+3)(x²-x-2)
计算 (x+3)(x²-x-2)
x/x-3-5x/x^2-x-6计算
计算:x/x-2 - 5x/x²-x-6计算:x/x-3 - 5x/x²-x-6
计算:x^2-9/4-x^2*x^2+x-2/x^2-4x+3,
x^2+x-6分之x^2+3x-x^2-4分之x+2计算
【计算(过程)】-x^2*(-x)^3+3x^3*(-x^2)-4(-x)*(-x)^4
4x²-[2x-(x²-2x+3)-2(x²-3x)] 计算
计算:(x-1)(x^2-4X+3)-x(x^2-5X+2)有过程